2019
DOI: 10.1002/ab.21868
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation mediates relationships between mindfulness facets and aggression dimensions

Abstract: Recent years have witnessed an increase of research on socio‐affective factors that can explain individual differences in aggressive tendencies across community and offender populations. Specifically, mindfulness and emotion regulation have emerged as important factors, which could also constitute important prevention and treatment targets. Yet, recent studies have advanced the possibility that mindfulness may also have a “dark” side, being associated with increased levels of aggression‐related variables, espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 53 publications
3
25
1
2
Order By: Relevance
“…This is further supported by impulse control and aggression control both individually having significant negative relationships with recidivism (although they did not remain significant predictors when adopting a stricter significance threshold to account for familywise error rate). In addition, our findings are in line with research supporting a link between emotion regulation and aggression (Garofalo, et al, 2018;Garofalo et al, 2019), as well as the effectiveness of interventions aimed at promoting emotional and cognitive regulation for reducing adult recidivism (Brazão et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is further supported by impulse control and aggression control both individually having significant negative relationships with recidivism (although they did not remain significant predictors when adopting a stricter significance threshold to account for familywise error rate). In addition, our findings are in line with research supporting a link between emotion regulation and aggression (Garofalo, et al, 2018;Garofalo et al, 2019), as well as the effectiveness of interventions aimed at promoting emotional and cognitive regulation for reducing adult recidivism (Brazão et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…Another study examined developmental trajectories of antisocial behavior and aspects of psychosocial maturity from adolescence to young adulthood in a sample of 1170 male youth involved in the juvenile justice system and found that improvements in impulse control and suppression of aggression were associated with decreased antisocial behavior, whereas there were no clear associations for other aspects of psychosocial maturity, such as personal responsibility and resistance to peer influence (Monahan et al, 2009). Previous research has identified the unique contributions of alexithymia, impulsivity, and emotion dysregulation in predicting aggression (Garofalo et al, 2018), and implicated emotion (dys)regulation as a mediating process between other cognitive/ attentional constructs (e.g., impulsivity, mindfulness, and moral disengagement) and aggression (Garofalo et al, 2016(Garofalo et al, , 2018(Garofalo et al, , 2019Long et al, 2014).…”
Section: Cognitive and Emotion Regulationmentioning
confidence: 99%
“…A higher dispositional mindfulness was also linked with more effective regulation of negative emotion (Modinos et al, 2010). Finally, another study on inmates and community samples indicated that emotional dysregulation, or the maladaptive pattern of emotion regulation strategies, mediated the relation between mindfulness and aggression (Garofalo et al, 2019).…”
Section: Emotion Regulation Strategies As Potential Mediatorsmentioning
confidence: 91%
“…Specifically, Gillespie and his colleagues (2018) found that violent offenders scored higher than the community sample on the observing facet of mindfulness. Observing was also positively correlated with emotion dysregulation and aggression (Garofalo et al, 2019). In this view, it could be argued that highly observing people are inadequate in emotion regulation, as the observing facet could be related to self-critical selfawareness where knowing the emotions being experienced may actually exacerbate the negative emotion (e.g., "I notice I am depressed.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…La conciencia plena se caracteriza por una actitud constante que permite estar atento y consciente de lo que sucede en el momento presente (Garofalo et al, 2020). En términos generales, está conformada por dos aspectos fundamentales.…”
unclassified